Analysis of the protrayal of law enforcement in selected films of Fernando Poe Jr. - Moncera, Ana Marie N. (2002.)
Research has suggested that the influence of the mass media in today?s world is so pervasive. Some studies also show that our perception of law enforcement institutions are affected by the mass media. Lately, law enforcement institutions expressed concerns about the way they are portrayed in films. Drawing on these, a study on the portrayal of law enforcement in selected films of Fernando Poe Jr was conducted. Characterizations of law enforcers in the thirteen films of FPJ where he plays the role of a law enforcer are recorded. The researcher also delved into literatures on the cultural politics of law enforcement and analyze the film?s portrayal of law enforcement using the film reflection theory. It was found out that FPJ films show representation of the cultural politics of law enforcement in the Philippines. They show us that law enforcers protect illegal activities and that law enforcement institutions suffer from poor credibility. They tell us that justice is hard to get in courts and so heroes like FPJ take the law into their own hands. However, it was also found out that these representations are not profound. Law enforcement issues are in most cases used only to show FPJ?s fighting skills. They are also inaccurate in that they show us the superhuman law enforcer, someone who always works, overly honest and have superb boxing and gun-slinging skills. They also show us that good law enforcers always defeat bad law enforcers. Finally, it was observed that the portrayal of law enforcement in FPJ?s films are restricted by the conventions of the Filipino action film genre or the so-called ?pelikulang bakbakan?.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2002.
Keywords: Poe, Fernando Jr. -- Films -- Research